First Principles Study of Undoped and Halogen Doped ZnO Monolayer (Journal of Nepal Physical Society, 2024)
This study reports the structural, electronic, and magnetic properties of undoped and halogen (F, Cl, and Br) doped ZnO monolayers (3 × 3 × 1) by replacing one Zn-atom. Using spin polarized Density Functional Theory (DFT) in VASP code and a projected augmented wave basis set, we employed GGA-PBE and PBE+U exchange correlation functionals. The band gap of pristine ZnO was measured to be 1.67 eV and 2.61 eV for PBE and PBE+U, respectively, whereas band gap decreased significantly upon addition of halogen atom. Likewise, doped ZnO shows semimetallic behavior, whereas undoped ZnO exhibits semiconducting behaviour. Further, the magnetic moments of about 1 µB for Cl and Br-doped ZnO, and 1.02 µB & 2.98 µB for F-ZnO utilizing PBE and PBE+U functionals, respectively were observed. These findings suggest that halogen-doped ZnO might carry huge potential for next-generation spintronic nanodevices.